1031Predictors of Lung function change over the life course: a systematic review. (2nd September 2021) - Okyere, Daniel; Waidyatillake, Nilakshi; Bui, Dinhi; Lowe, Adrian; Perret, Jenny; Lodge, Caroline; Dharmage, Shyamali
Abstract: Background: Throughout life, lung function increases, peaks, plateaus and declines. These phases can be influenced by several exposures. Despite the growing body of evidence, the association between these factors and lung function change over the lif course has not been systematically reviewed. Methods: Using a pre-defined protocol, two authors independently identified publications related to lung function trajectories and extracted relevant information. We included studies that identified/developed/modelled/reported lung function trajectories based on at least three-time points. Due to heterogeneity in the exposures and methods used to model lung function trajectories, it was not possible to conduct a meta-analysis. Results: A total of 12 population-based cohort studies met the inclusion criteria. Of these, 10 were birth cohorts. 4 studies used cluster analysis techniques to develop trajectories while the others used generalized linear interactive modelling. Eight factors were identified, by 2 or more studies, as predictors for reduced lung growth, decline and/or persistently low trajectories. They were low birth weight and parental asthma (n = 2); childhood asthma and allergic sensitization (n = 4); childhood lower respiratory tract infections and childhood persistent wheezing, and environmental tobacco smoke (n = 3); and childhood eczema (n = 2). Conclusions: Our review identified risk factors for lung function change that have been consistent at least across two studies. Key messages: These findings suggest preventive measures directed at childhood asthma and infections, and tobacco exposure will help promote lung health and prevent unhealthy lung function trajectories.